2021
DOI: 10.23887/jjpf.v11i1.24501
|View full text |Cite
|
Sign up to set email alerts
|

Pemahaman Siswa Tentang Aplikasi Konsep Suhu Dan Kalor Yang Berkaitan Dengan Komputer

Abstract: Berbeda dengan level pendidikan menengah lainnya, pembelajaran fisika di SMK Teknik memiliki kewajiban lebih yaitu untuk mengintegrasikan konsep-konsep fisika dalam bidang keahliannya. Tujuan utama penelitian ini adalah untuk mengetahui bagaimana pemahaman siswa terkait aplikasi konsep suhu dan kalor yang berkaitan dengan komputer. Jenis penelitian ini adalah penelitian deskriptif kuantitatif dengan metode studi kasus. Subjek penelitian terdiri atas 36 siswa teknik komputer dan jaringan (TKJ), SMK Al Munawwari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
9
0
2
Order By: Relevance
“…The low level of understanding of the concept of work in mathematical representation is in line with the results of research (Mustofa et al, 2016), which states that students' understanding of the basic concepts of mechanical energy about work as a result of dot multiplication between force and displacement is still very low. Some students also have misconceptions about effort and difficulty in determining the dot (Barniol & Zavala, 2014) product.…”
Section: Figure 1 Question With Sub-topics Of Work In Mathematical Re...supporting
confidence: 75%
See 2 more Smart Citations
“…The low level of understanding of the concept of work in mathematical representation is in line with the results of research (Mustofa et al, 2016), which states that students' understanding of the basic concepts of mechanical energy about work as a result of dot multiplication between force and displacement is still very low. Some students also have misconceptions about effort and difficulty in determining the dot (Barniol & Zavala, 2014) product.…”
Section: Figure 1 Question With Sub-topics Of Work In Mathematical Re...supporting
confidence: 75%
“…The reasons expressed by students in answering the questions above also indicate that students still have limited mathematical abilities which hinder them in solving physics problems (Haryadi, 2016;Nurlailiyah & Delta, 2015;Rusilowati, 2006). This is supported by previous research which revealed that there were several errors experienced by students in solving kinetic energy problems, namely: 1) students were not able to use the equation for the relationship between work and kinetic energy; 2) students are not yet able to identify systems and model them to apply the work -kinetic energy theorem; 3) students assume that the slope of the path an object passes has an effect on changes in the object's kinetic energy; 4) students assume that moving objects are always caused by a resultant force or effort that is not zero (Mustofa et al, 2016).…”
Section: Figure 2 Question With Sub-topics Of Kinetic Energy In Mathe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pusat Kegiatan Belajar Masyarakat (PKBM) adalah sebuah lembaga pendidikan yang diselenggarakan di luar sistem pendidikan non formal diarahkan untuk masyarakat pedesaan dan perkotaan dengan dikelolah oleh masyarakat itu sendiri serta memberi kesempatan kepada mereka untuk mengembangkan berbagai model pembelajaran dengan tujuan mengembangkan berbagai model pembelajaran dengan tujuan mengembangkan kemampuan dan keterampilan masyarakat agar mampu meningkatkan kualitas hidupnya (Mustofa, 2010). Pengembangan konsep PKBM haruslah memperhatikan dua faktor secara bersamaan yaitu faktor kemampun konsep dalam menjelaskan secara lengkap dan utuh seluruh eksistensi dan karakteristik PKBM itu sendiri dan faktor kemampuan konsep dalam mengakomodasikan berbagai perkembangan dan keragaman PKBM baik yang telah ada maupun yang akan datang.…”
Section: Telaah Pustaka a Pusat Kegiatan Belajar Masyarakatunclassified
“…Based on the identification results of previous research, it was found that there were several forms of misconceptions experienced by students in the matter of temperature and heat, including students who assumed that hot and cold could move, and on the concept of temperature students assumed that cold objects did not contain heat. There are several reasons that cause these problems, namely the temperature material is an abstract material, the concept of heat has many influencing factors and each factor should not be omitted, and students often bring their understanding in everyday life contrary to the concept of temperature and heat understood by experts (Mustofa, 2021). The problems above are the difficulties experienced by students in general regarding the concepts of temperature and heat.…”
Section: Introductionmentioning
confidence: 99%